Gender’s Influence on Risk-Taking Behavior: Insights from Game-Based Decision Making - Pudjoharsoyo, Achmad Setyo (Journal of Global Economy, Business and Finance, 2025)
The research project investigates how gender influences risk aversion and gaming - related decision making. A sample of fifteen people, ages 24 to 47, from the Delhi - NCR area are used in the study. Five games, each with two rounds, were intended for the players to play. Male and female participants engaged in a bidding process wherein financial gains and losses were decided by strategic decisions. The study's findings indicate that men were more daring and regularly placed higher bids, whereas women were more conservative and adjusted their offers to minimize losses. In addition to winning more games, male players also lost more games on occasion. The study demonstrates the fascinating role that gender plays in risk - taking behaviors, which has implications for comprehending patterns of economic decision making.